Impairment of FtsHi5 Function Affects Cellular Redox Balance and Photorespiratory Metabolism in Arabidopsis. (21st August 2018) - Wang, Ting; Li, Sihui; Chen, Dan; Xi, Yue; Xu, Xuezhong; Ye, Nenghui; Zhang, Jianhua; Peng, Xinxiang; Zhu, Guohui
Abstract: Photorespiration is an essential process for plant photosynthesis, development and growth in aerobic conditions. Recent studies have shown that photorespiration is an open system integrated with the plant primary metabolism network and intracellular redox systems, though the mechanisms of regulating photorespiration are far from clear. Through a forward genetic method, we identified a photorespiratory mutant pr1 ( p hotorespiratory r elated 1 ), which produced a chlorotic and smaller photorespiratory growth phenotype with decreased chlorophyll content and accumulation of glycine and serine in ambient air. Morphological and physiological defects in pr1 plants can be largely abolished under elevated CO2 conditions. Genetic mapping and complementation confirmed that PR1 encodes an FtsH (Filamentation temperature-sensitive H)-like protein, FtsHi5. Reduced FtsHi5 expression in DEX-induced RNAi transgenic plants produced a similar growth phenotype with pr1 ( ftsHi5-1 ). Transcriptome analysis suggested a changed expression pattern of redox-related genes and an increased expression of senescence-related genes in DEX: RNAi-FtsHi5 seedlings. Together with the observation that decreased accumulation of D1 and D2 proteins of photosystem II (PSII) and over-accumulation of reactive oxygen species (ROS) in ftsHi5 mutants, we hypothesize that FtsHi5 functions in maintaining the cellular redox balance and thus regulates photorespiratory metabolism.